PENGARUH KONSELING GIZI TERHADAP PENGETAHUAN ORANG TUA BALITA DI POSYANDU WILAYAH KERJA UPTD PUSKESMAS KOTANOPAN - Harahap, Mei Adelina; Fitri Napitupulu, Natar; Ritonga, Nefonavratilova; Rangkuti, Juni Andriani (Universitas Aufa Royhan, 2025)
ABSTRACT Knowledge is the result of human sensing, or the result of someone knowing objects through their senses). Knowledge itself is influenced by formal education factors. The purpose of this study was to determine the effect of nutrition counseling on the knowledge of parents of toddlers. This research method is quantitative with a quasi-experiment design with a one group pretest and posttest design, the population in this study amounted to 1,920 people with a sample of 95 respondents. The results of this study are the age characteristics of the majority of productive respondents (aged 20-35 years) 50.5%, the majority of female gender 100%, the majority of low education (elementary / junior high school) 48.4%, the majority of respondents' jobs are working 54.7%, and the majority of low income (˂ Rp. 2,691,808) 76.8%. The bivariate results showed that the comparison of knowledge before and after nutrition counseling from the results of the Wilcoxon statistical test obtained p-value = 0.001 (p <0.05), it can be concluded that there is a significant effect on nutrition counseling on knowledge. The conclusion of this study is that nutrition counseling needs to be done to improve the knowledge of parents of toddlers.